2016
DOI: 10.30843/nzpp.2016.69.5885
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest foliar nitrogen applications increase <i>Neonectria ditissima</i> leaf scar infection in apple trees

Abstract: Postharvest foliar nitrogen (urea) is often applied to apple leaves immediately after picking for bud fertilising and/or during leaf fall for Venturia inaequalis control During 20132016 ethylene diamine tetraacetic acid copper (EDTACu to enhance leaf abscission) urea calcium nitrate and BudWiser foliar treatments were applied alone or in combination to determine their effects on leaf scar infection by Neonectria ditissima in Braeburn (201314) Scifresh and Royal Gala (201516) orchards In 201314 leaf scar infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…The number of leaf scars showing symptoms was low, as was the case in 2015 (Dryden et al 2016;Walter et al 2017b). Only 7.9% of inoculated shoots expressed disease, with an average of 1.4 leaf scars/shoot developing symptoms.…”
Section: Lesion Development From Leaf Scarsmentioning
confidence: 89%
See 4 more Smart Citations
“…The number of leaf scars showing symptoms was low, as was the case in 2015 (Dryden et al 2016;Walter et al 2017b). Only 7.9% of inoculated shoots expressed disease, with an average of 1.4 leaf scars/shoot developing symptoms.…”
Section: Lesion Development From Leaf Scarsmentioning
confidence: 89%
“…Parallel grower experiments on three sites (data not shown) indicated that this is generally achieved using standard orchard sprayers with water rates of 1000 L/ha. The low expression of leaf-scar infections is disappointing, but this has occurred in other artificially inoculated and naturally infected leaf-scar experiments in the 2015 autumn-winter period (Dryden et al 2016;Walter et al 2017b). Normally, under New Zealand (Tasman) conditions, we would expect 10-20% of leaf scars to develop symptoms within 6 months of artificial inoculation Walter et al 2015;2017b) but in the 2015 autumn-spring period only 4.4 % of leaf scars expressed in the control treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations